The role of poly(ADP-ribose)polymerase in the induction of sister chromatid exchanges and micronuclei by mitomycin C in Down's syndrome cells as compared to euploid cells - Caria, Helena (2017)
Inhibitors of poly(ADP-ribose)polymerase (PARP; EC 2.4.2.30), such as 3-aminobenzamide (3-AB), can be used to assess the role of the enzyme in the induction of DNA lesions in euploid cells as compared to cells of genetic conditions known to exhibit increased susceptibility to chemical or physical mutagens, such as Down’s syndrome (DS) lymphocytes. We report in this work on the effect of PARP inhibition by 3-AB in the induction of sister chromatid exchanges (SCE) and micronuclei (MN) in DS lymphocytes as compared to iymphocytes from normal controls exposed in vitro to a gradient of mitomycin C (MMC). For both tvpes of cells, DS and normal lymphocytes. MMC induces a significant increase in frequencies of SCE and MN in the absence and in the presence of 3-AB. In the presence of 3-AB the yield of SCE and MN induced by MMC was significantly higher in normal lymphocytes as compared to lymphocytes from DS patients. The molecular mechanisms by which 3-AB affects the yield of SCE and MN remains to be fully elucidated: however, it seems clear that DS patients display a diftèrent behavior in what concerns poly(ADP-ribosyl)ation as compared to normal individuais.